Penggunaan daun ketumbar (coriandrum sativum L.) sebagai penjernih air di Desa Meka Praya Tengah - Pahrurrozi Pahrurrozi; Dwi Agustini; Rio Satriyantara (Rengganis Jurnal Pengabdian Masyarakat, 2021)
Abstract Water is the principal human needs. Utilization in all life aspect. However water availability in every area is different. Meka Village with location in Central Praya Distric Central Lombok usually deficiency of clean water in dry season. Public make use of surface water to fulfill needs. This community dedication aim at give society way to process and use coriander leaves as ingredient water clarifier. Coriander leaves have absorbs ability to solute in the water and have antioxsidants coumpound. This proven that application coriander leaves able to lowered water temperature amounting to 3,4 ℃ and ph amounting to 5,4. Based on these research could concluded that coriander leaves able to clarifier water because have nature to absorbs solute in the water and also contain antioxidants compound